UPAYA MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA DALAM PEMBELAJARAN IPA DENGAN MENGGUNAKAN MODEL PROJECT BASED LEARNING DI KELAS V SEKOLAH DASAR - Solehuddin; Khoimatun; Ririn Andriani Kumala Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This research is motivated by the completeness of student learning outcomes in science subjects that have not been maximized, namely 27 students (63%) have not reached the KKM. This is because the learning process is still dominated by the teacher, students are less involved in the learning process. One of the efforts made is to update the learning model by using the Project Based Learning model. This study aims to determine the application of the PjBL learning model in science subjects, to determine the increase in learning activities and learning outcomes of grade V students of UPTD SD Negeri 1 Tanjungsari. The research method used is Classroom Action Research (PTK) with three cycles consisting of four steps, namely: planning, implementation, observation and reflection. This research was applied to grade V students with a total of 43 students. The results of the application of the Project Based Learning (PjBL) learning model increased in each cycle. In cycle I, 81.53% of the good category, cycle II, 87.69% of the very good category and cycle III, 94.61% of the very good category. The results of student activity also increased in each cycle. In cycle I, 67.57% of the moderate category, cycle II 79.81% of the good category, in cycle III 86.36% of the very good category. Student learning outcomes obtained during the action implementation process have increased in each cycle. In cycle I there were 23 students with a percentage of 53.49% of students completed, cycle II there were 37 students with a percentage of 86.05% students completed, and cycle III there were 38 students with a percentage of 88.37% students completed. This research shows that student learning outcomes reach the 80% classical success indicator. Based on the results of the study, it shows that the application of the Project Based Learning learning model in science subjects in grade V elementary schools can improve student learning activities and results. Keywords: project based learning, science, activity, learning outcomes